An analysis of citations of IRRI scholars' doctoral dissertations, 1991-2000 - Manlangit, Rene B. (2008)
The purpose of this study was to investigate the pattern of citations in IRRI scholars' doctoral dissertations submitted to the University of the Philippines Los Baños for the period 1991-2000 by using citation analysis as the methodology to determine the characteristics of the materials cited by IRRI scholars.